2007
DOI: 10.1093/ecam/nem151
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinium myrtillus (Bilberry) Extracts Reduce Angiogenesis In Vitro and In Vivo

Abstract: Vaccinium myrtillus (Bilberry) extracts (VME) were tested for effects on angiogenesis in vitro and in vivo. VME (0.3–30 µg ml−1) and GM6001 (0.1–100 µM; a matrix metalloproteinase inhibitor) concentration-dependently inhibited both tube formation and migration of human umbilical vein endothelial cells (HUVECs) induced by vascular endothelial growth factor-A (VEGF-A). In addition, VME inhibited VEGF-A-induced proliferation of HUVECs. VME inhibited VEGF-A-induced phosphorylations of extracellular signal-regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 27 publications
3
44
0
2
Order By: Relevance
“…After the medium exchange, anthocyanidins were capable of inhibiting VEGF-induced intracellular signaling within a few hours (before degradation of anthocyanidin). It was reported that VMA inhibits VEGF-induced activation of intracellular signaling, ERK1/2 (within 5 min) and Akt (within 10 min) (Matsunaga et al, 2007). It was considered that VMA can promptly inhibit the VEGFinduced signaling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After the medium exchange, anthocyanidins were capable of inhibiting VEGF-induced intracellular signaling within a few hours (before degradation of anthocyanidin). It was reported that VMA inhibits VEGF-induced activation of intracellular signaling, ERK1/2 (within 5 min) and Akt (within 10 min) (Matsunaga et al, 2007). It was considered that VMA can promptly inhibit the VEGFinduced signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that VMA reduced both in vitro and in vivo angiogenesis (Matsunaga et al, 2007). Further, it was indicated that its effect may be due in part to reductions in cell proliferation and migration through inhibitions of both phosphorylated extracellular signal-regulated kinase 1/2 (ERK 1/2) and serine/ threonine protein kinase family protein kinase B (Akt) (Matsunaga et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this anecdote itself is not evidence-based, and several clinical studies failed to verify the above claim (Levy and Glovinsky, 1998;Zadok et al, 1999;Muth et al, 2000; Canter and Ernst, 2004). On the other hand, bilberry anthocyanins have been shown to exhibit neuroprotective effects in ocular tissue and suppressive effects on diabetic retinopathy via a reduction of angiogenesis (Matsunaga et al, 2010a(Matsunaga et al, , 2010b. Furthermore, several studies have demonstrated that blackcurrant anthocyanins (BA) improve visual function; for example, BA inhibit transient myopia, reduce eye fatigue, improve dark adaptation, and increase retinal blood flow in glaucoma (Nakaishi et al, 2000;Ohguro et al, 2007; Iida et al, 2010).…”
Section: Challenges In and Prospect For Anthocyanin Researchmentioning
confidence: 99%